Cost-effectiveness of ceftolozane/tazobactam plus metronidazole compared with piperacillin/tazobactam as empiric therapy for the treatment of complicated intra-abdominal infections based on the in-vitro surveillance of bacterial isolates in the UK. (3rd August 2017) - Prabhu, Vimalanand; Foo, Jason; Ahir, Harblas; Sarpong, Eric; Merchant, Sanjay
Abstract: Aims: An increase in the prevalence of antimicrobial resistance among gram-negative pathogens has been noted recently. A challenge in empiric treatment of complicated intra-abdominal infection (cIAI) is identifying initial appropriate antibiotic therapy, which is associated with reduced length of stay and mortality compared with inappropriate therapy. The objective of this study was to assess the cost-effectiveness of ceftolozane/tazobactam + metronidazole compared with piperacillin/tazobactam (commonly used in this indication) in the treatment of patients with cIAI in UK hospitals. Methods: A decision-analytic Monte Carlo simulation model was used to compare costs (antibiotic and hospitalization costs) and quality-adjusted life years (QALYs) of patients infected with gram-negative cIAI and treated empirically with either ceftolozane/tazobactam + metronidazole or piperacillin/tazobactam. Bacterial isolates were randomly drawn from the Program to Assess Ceftolozane/Tazobactam Susceptibility (PACTS) database, a surveillance database of non-duplicate bacterial isolates collected from patients in the UK infected with gram-negative pathogens. Susceptibility to initial empiric therapy was based on the measured susceptibilities reported in the PACTS database. Results: Ceftolozane/tazobactam + metronidazole was cost-effective when compared with piperacillin/tazobactam, with an incremental cost-effectiveness ratio (ICER) of £4, 350/QALY and 0.36 hospitalization days/patient saved. Costs in the ceftolozane/tazobactam + metronidazole arm were £2, 576/patient, compared with £2, 168/patient in the piperacillin/tazobactam arm. The ceftolozane/tazobactam + metronidazole arm experienced a greater number of QALYs than the piperacillin/tazobactam arm (14.31/patient vs 14.21/patient, respectively). Ceftolozane/tazobactam + metronidazole remained cost-effective in one-way sensitivity and probabilistic sensitivity analyses. Conclusions: Economic models can help to identify the appropriate choice of empiric therapy for the treatment of cIAI. Results indicated that empiric use of ceftolozane/tazobactam + metronidazole is cost-effective vs piperacillin/tazobactam in UK patients with cIAI at risk of resistant infection. This will be valuable to commissioners and clinicians to aid decision-making on the targeting of resources for appropriate antibiotic therapy under the premise of antimicrobial stewardship.